2016
DOI: 10.3892/ijmm.2016.2772
|View full text |Cite
|
Sign up to set email alerts
|

Amentoflavone protects against high fat-induced metabolic dysfunction: Possible role of the regulation of adipogenic differentiation

Abstract: In the present study, we evaluated the protective effects of amentoflavone (AMF) against high-fat (HF) diet-induced metabolic dysfunction and focused on the influence of AMF on adipogenic differentiation during 3T3-L1 adipocyte differentiation. For this purpose, male Wistar rats were fed a HF diet or a HF diet with AMF (10 or 50 mg/kg). We found that AMF protected against HF diet-induced metabolic dysfunction in a dose-dependent manner, as evidenced by a decrease in the fasting blood glucose levels, fasting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…We observed that NAC inhibited phosphorylation of mitogen-activated protein kinases in cell cultures [7,16] on the first day of differentiation protocol; this finding was consistent with another study using a known antioxidant such as epigallocatechin gallate [17]. We also demonstrated that NAC induced a decrease in PPARγ protein expression on the fourth day of differentiation process [5], similar to other groups, which confirmed that NAC blocks lipid accumulation by reducing cellular PPARγ protein expression during adipocyte differentiation [18][19][20]. However, the effects of NAC related with PPARγ in mature adipocytes have not yet been studied, which it is essential because adipose tissue is mainly composed of mature adipocytes and in a low percentage by differentiating precursor cells.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that NAC inhibited phosphorylation of mitogen-activated protein kinases in cell cultures [7,16] on the first day of differentiation protocol; this finding was consistent with another study using a known antioxidant such as epigallocatechin gallate [17]. We also demonstrated that NAC induced a decrease in PPARγ protein expression on the fourth day of differentiation process [5], similar to other groups, which confirmed that NAC blocks lipid accumulation by reducing cellular PPARγ protein expression during adipocyte differentiation [18][19][20]. However, the effects of NAC related with PPARγ in mature adipocytes have not yet been studied, which it is essential because adipose tissue is mainly composed of mature adipocytes and in a low percentage by differentiating precursor cells.…”
Section: Introductionsupporting
confidence: 91%
“…Other authors that have used NAC during adipocyte differentiation, reported similar results [18,20,38,39]. Therefore, we could speculate about a possible use of this molecule as a new drug or as an adjuvant to decrease lipid content in human adipose tissue during obesity development.…”
Section: Discussionsupporting
confidence: 72%
“…AMF also protects against liver dysfunction through increasing GSH, SOD level and CAT activities, and decreasing NADPH oxidase activities (Qin et al, 2018). In addition, Chen et al (2016) demonstrate that AMF can protect against high fat dietinduced metabolic dysfunction and inhibit 3T3-L1 adipocyte differentiation. Mechanically, AMF not only promotes ROS generation, but also decreased CCAAT/enhancer-binding protein (C/EBP) β expression, and results in the inhibition of mitotic clonal expansion (MCE) (Chen et al, 2016).…”
Section: Metabolism Regulationmentioning
confidence: 88%
“…Fasting mice were orally administered 200 μL of glucose at a dose of 1 g/kg body weight. Blood was collected from the tail vein, and the blood glucose level was determined using an AccuChek Active Kit (Roche Diagnostics, Mannheim, Germany) at 0, 15, 30, 60, and 120 min after glucose challenge [33].…”
Section: Methodsmentioning
confidence: 99%